High Ankle–Brachial Index Indicates Cardiovascular and Peripheral Arterial Disease in Patients With Type 2 Diabetes. (November 2015) - Li, Qing; Zeng, Hui; Liu, Fang; Shen, Jing; Li, Lianxi; Zhao, Jungong; Zhao, Jun; Jia, Weiping
We assessed the association between high ankle–brachial index (ABI) and cardiovascular disease (CVD) and peripheral arterial disease (PAD) in Chinese patients with type 2 diabetes mellitus (T2DM). The ABI was measured, and foot inspection was performed in 2080 outpatients with T2DM. The clinical characters in different ABI levels were analyzed, and the diagnostic value of high ABI to CVD and PAD was determined. Compared with the normal ABI group, the high ABI (>1.3) group had a higher prevalence of CVD and PAD but less than the low ABI (≤0.9) group. High ABI was an independent risk factor for the development of CVD and PAD. Receiver–operating characteristic curve analysis showed that the optimal cutoff of high ABI to predict CVD and PAD was 1.43 and 1.45, respectively. The odds ratio of high ABI for CVD and PAD was 2.25 and 6.97, respectively, after adjusting for other confounding risk factors. In conclusion, high ABI indicated the risk of CVD and PAD in Chinese populations with T2DM.